Implementasi Nilai Pancasila Dalam Pembentukan Undang-Undang - Frensiska Ardhiyaningrum (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This essay emphasizes the significance of implementing Pancasila values into law-making methods in Indonesia. Pancasila, being the foundation of the state, offers notions that can be used as guidance for ethical and moral laws. This qualitative study explores how Pancasila values like social justice, unity, and deliberation are applied in lawmaking. This article looks at legislation that show inconsistent implementation of Pancasila ideals and are often impacted by political and economic considerations. This article identifies barriers to adopting Pancasila values into public policy and suggests strategies to promote public participation in the legislative process. The goal is to raise knowledge of and apply Pancasila values so that the law better represents societal aspirations and promotes social fairness.